2015
DOI: 10.1084/jem.20141518
|View full text |Cite
|
Sign up to set email alerts
|

ICOS and Bcl6-dependent pathways maintain a CD4 T cell population with memory-like properties during tuberculosis

Abstract: Protective CD4 T cells specific for M. tuberculosis (Mtb) are maintained in the lungs during active Mtb infection. Similar to memory CD4 T cells, persistence of these Mtb-specific cells requires intrinsic expression of Bcl6 and ICOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
138
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(154 citation statements)
references
References 57 publications
16
138
0
Order By: Relevance
“…The expression of genes RBBP8 , RAB13 , FCGR1A , TIMM10 and SMARCD3 has been demonstrated to significantly distinguish between active TB and other diseases such as sarcoidosis and pneumonia (patent WO2014093872 A1). BCL6 has been shown to mediate a sustained Mtb specific CD4 T cell response in addition to regulating host apoptotic responses (Moguche et al, 2015). Both IFI44L and SLPI participate in the interferon-mediated inflammation in TB (Maji et al, 2015), with IFI44L also implicated in lymph node tuberculosis; SLPI has been shown to exhibit antimicrobial activity and also plays an important role in regulating apoptosis by interacting with membrane phospholipid scramblase (Py et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of genes RBBP8 , RAB13 , FCGR1A , TIMM10 and SMARCD3 has been demonstrated to significantly distinguish between active TB and other diseases such as sarcoidosis and pneumonia (patent WO2014093872 A1). BCL6 has been shown to mediate a sustained Mtb specific CD4 T cell response in addition to regulating host apoptotic responses (Moguche et al, 2015). Both IFI44L and SLPI participate in the interferon-mediated inflammation in TB (Maji et al, 2015), with IFI44L also implicated in lymph node tuberculosis; SLPI has been shown to exhibit antimicrobial activity and also plays an important role in regulating apoptosis by interacting with membrane phospholipid scramblase (Py et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of CXCR5, mice fail to develop iBALT and are more susceptible Mtb (459) with the impaired response being rescued through the adoptive transfer of CXCR5-sufficient T cells, suggesting that CXCR5 expression on T cells is important for both protection and the development of B cell follicles. Further, CXCR5 is required for the maintenance Mtb-specific CD4 + T cells during chronic infection (81). B cells from Mtb infected murine lungs are also able to migrate along a CXCL13 chemotactic gradient in vitro via their expression of CXCR5 (463).…”
Section: The Chemokinesmentioning
confidence: 99%
“…In addition, expression of PD-1 and CXCR3 in absence of KLRG-1 facilitates access of these cells to lesions [142]. Such memory-like PD-1 + T cells [143] populate the lesions and are protective in murine TB. Memory CD4 + lymphocytes have been confirmed at the core of human TB granulomas [144] while granulysin/ perforin low-expressing CD8 + T cells populate the outer lymphocyte mantel of granulomas [145].…”
Section: Granuloma: Good For Host and Pathogenmentioning
confidence: 99%